Elucidation of the Electrochemical Reaction Mechanism in MFe2O4 (M=Ni, Co) Conversion‐Type Negative Electrode Systems by using In Situ X‐ray Absorption Spectroscopy. Issue 10 (14th July 2015) - Balachandran, Geethu; Dixon, Ditty; Bramnik, Natalia; Bhaskar, Aiswarya; Yavuz, Murat; Pfaffmann, Lukas; Scheiba, Frieder; Mangold, Stefan; Ehrenberg, Helmut
Abstract Mixed transition‐metal ferrites with the chemical formula MFe2O4 (M=Co, Ni), synthesized through an inverse co‐precipitation route, were characterized by using scanning electron microscopy and powder X‐ray diffraction, which demonstrate phase‐pure compounds with particle sizes of about 100 nm. Cyclic voltammetry investigations in lithium half‐cells revealed a difference between the first cycle and the following charge–discharge cycles, which is characteristic for conversion‐type electrode systems. To understand the mechanism of the electrochemical reaction in the first cycle, in situ X‐ray absorption spectroscopy was performed during cycling at a charge–discharge rate of C/10. During the first discharge process, the crystalline Co and Ni ferrites undergo reduction. A coexistence of binary metal oxides (CoO/NiO and Fe2O3) and metallic phases were observed during the discharge. At the end of discharge, only the existence of metallic nanoclusters was observed. In the subsequent charging process, Fe was found to undergo complete oxidation in both ferrites. In contrast, almost 60 % of the Co or Ni remained in the metallic state at the end of the charge (end of first cycle). This incomplete oxidation of Co and Ni in the applied voltage range could be the main reason behind the irreversible capacity loss and low coulombic efficiency often reported for these conversion electrode systems.